Preparation and Spectral Characterization of New Azo Imidazole Ligand 2-[(2`-Cyano Phenyl) Azo]-4,5-Diphenyl Imidazole and its Complexes with Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg (II) Ions - Baghdad Science Journal (مجلة بغداد للعلوم)
The preparation and spectral characterization of complexes for Co(II), Ni(II), Cu(II), Cd(II), Zn(II) and Hg(II) ions with new organic heterocyclic azo imidazole dye as ligand 2-[(2`-cyano phenyl) azo ]-4,5-diphenyl imidazole ) (2-CyBAI) were prepared by reacting a dizonium salt solution of 2-cyano aniline with 4,5-diphenyl imidazole in alkaline ethanolic solution .These complexes were characterized spectroscopically by infrared and electronic spectra along with elemental analysis‚ molar conductance and magnetic susceptibility measurements. The data show that the ligand behaves a bidantate and coordinates to the metal ion via nitrogen atom of azo and with imidazole N3 atom. Octahedral environment is suggested for all metal complexes.